INTERNET ENTREPRENEURSHIP IN THE IRAQI RESTAURANT INDUSTRY - Jafari Titkanloo, Saeed; Jawad Dakhel, Ahmed (The journal of contemporary issues in business and government, 2024)
With the corona virus epidemic, people's lifestyle changed. Many industries and services, including the restaurant industry, faced serious problems. And this increased the interest in internet entrepreneurship as a possible solution. In this regard, the main goal of the current research is to investigate the impact of some dimensions of Internet entrepreneurship on the purchase intention of customers in the restaurant industry of Iraq. This research has been carried out with a practical purpose and in a descriptive-survey manner. The statistical population of this research is all customers of online food ordering websites in Iraq, whose number of users is unknown and more than 10,000 people. The sampling method is available and based on Morgan's table, 384 people were considered as the sample size. A questionnaire was used to collect information. The validity of the questionnaire was confirmed by referring to experts' opinions and factor analysis. Cronbach's alpha method was also used to measure reliability. Then, the relationship between the variables was analyzed by the method of structural equations in Smart pls software. The results showed that the visual attractiveness of online menus, the sufficiency of online menu information, the perception of risk-taking have a positive and significant effect on consumers' willingness to order food online in Iraq. The perception of risktaking has a positive and significant effect on the perceived convenience of consumers of online restaurant stores in Iraq. The convenience of customers to order food online and the desire of consumers have a positive and significant effect on the purchase intention of customers of online restaurant stores in Iraq.